2017
DOI: 10.1016/j.toxicon.2017.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the presence of marine toxins in bivalve molluscs from southwest India

Abstract: The south west coast of India has been showing a steady increase in shellfish cultivation both for local consumption and fishery export, over recent years. Perna viridis and Crassostrea madrasensis are two species of bivalve molluscs which grow in some selected regions of southern Karnataka, close to the city of Mangalore. In the early 1980s, shellfish consumers in the region were affected by intoxication from Paralytic Shellfish Poison present in local bivalves (clams and oysters) resulting in hospitalisation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Similar to other phycotoxins, a high content of GYMs can accumulate in bivalve mollusks, including in scallops, mussels, oysters, and clams. Shellfish samples contaminated by Toxins 2021, 13, 793 2 of 14 GYMs have been reported in China [8,9], Europe [10,11], Lebanon [12], Mexico [13] and India [14]. Even though a regulatory limit for GYMs in shellfish has not been adopted due to lack of knowledge regarding their toxicological effects on human health, this toxin group has been evaluated by EFSA [15].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to other phycotoxins, a high content of GYMs can accumulate in bivalve mollusks, including in scallops, mussels, oysters, and clams. Shellfish samples contaminated by Toxins 2021, 13, 793 2 of 14 GYMs have been reported in China [8,9], Europe [10,11], Lebanon [12], Mexico [13] and India [14]. Even though a regulatory limit for GYMs in shellfish has not been adopted due to lack of knowledge regarding their toxicological effects on human health, this toxin group has been evaluated by EFSA [15].…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has suggested that clams including Meretrix spp. may have a degree of resistance to PST uptake (Lu and Hwang, 2002), but other studies have reported very high PST levels of >3240 μg STX eq kg −1 , e.g., from Meretrix casta during a HAB outbreak in southwest India (Karunasagar et al, 1984). However, the results presented in this study, together with results of previous studies suggest that further work is required to fully understand the mechanistic effects of multiple climate change drivers on uptake and detoxification rates by commercially important bivalves.…”
Section: Discussionmentioning
confidence: 99%
“…PSTs can be transported and bioaccumulated in shellfish through the food chain before being consumed by humans [2]. Previous studies have shown that shellfish contamination with PSTs is a major health challenge in many coastal areas, such as Malaysia [22], Tasmania [23], India [24], and Venezuela [25]. Recently, high PST levels exceeding regulatory limits have been detected in shellfish from southeastern China, affecting seafood safety for consumers [19].…”
Section: Introductionmentioning
confidence: 99%